Developing a novel flavoured low alcohol beer using New Zealand honeydew honey and yacon concentrate - Keegan Chessum; Nazimah Hamid; Barry Wong; Tony Chen; Mary Yan; Rothman Kam (Applied Food Research)
Demand for low alcohol beer (LAB) is growing around the world as consumer attitudes towards alcohol consumption shift, with health consciousness and sober driving listed among the possible drivers. In New Zealand, LAB is defined as having no >1.15 % alcohol by volume (ABV). In industry, physical or biological processes are used to produce no- and low- alcohol beer; however, these methods are typically inaccessible to home brewers, and literature on accessible methods is non-existent. New Zealand honeydew honey (NZHDH) and New Zealand yacon concentrate (NZYC) have recently been chemically profiled in the literature. NZHDH and NZYC contain fermentable sugars, while NZYC also contains a very high percentage of fructooligosaccharides (FOS). This paper aims to incorporate these food materials into LABs using a method accessible to home brewers. The resultant LABs had an alcohol content between 0.61 and 0.86 % ABV, well under the 1.15 % threshold. Results from sensory analysis showed that all beer samples were somewhat acceptable to consumers; however, penalty analysis determined that hedonic scores could be improved by making the beers more sweet, bitter, and hoppy. Correspondence analysis revealed that the beers containing NZYC were more ‘foamy’ and ‘brown’ than all other beer samples, properties most likely related to the protein content and colour of NZYC respectively. Beers containing NZYC were also found to contain FOS and/or inulins, which are non-digestible sugars and therefore hypocaloric. This study provides an accessible method to produce LAB and shows how NZYC may be incorporated into LABs to yield a functional food.